Penggembalaan Jemaat Gereja Kristen Setia Indonesia (GKSI), Getsemani Palah Parajo Berdasrkan Matius 6:33 - Melkisedek Melkisedek (Lembaga Pengembangan Kinerja Dosen, 2025)
Pastoral ministry plays a crucial role in shaping the spiritual growth of the congregation so that they live according to the principles of the Kingdom of God. In practice, many congregations do not fully understand the meaning of Matthew 6:33, so its values are merely spiritual slogans without concrete application in daily life. This study aims to design a more effective pastoral strategy within the GEREJA KRISTEN SETIA INDONESIA (GKSI) Getsemani Palah Parajo, focusing on five main aspects: (1) a theological understanding of Matthew 6:33 as the basis for pastoral care; (2) the role of the pastor and congregation in building healthy relationships; (3) identifying the congregation's spiritual needs and challenges; (4) developing contextual pastoral strategies and methods; and (5) evaluating the congregation's spiritual growth. Through this approach, it is hoped that pastoral care will become a means of forming Christ-like character, which is not only theologically relevant but also has a real impact on the congregation's daily lives.